Consecutive Bites on Two Persons by Same Krait Snake: Two Fatal Case Series with Traditional Treatment (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 31-34 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15034